2020
DOI: 10.1002/app.49382
|View full text |Cite
|
Sign up to set email alerts
|

Comparative impact of SiO2 and TiO2 nanofillers on the performance of thin‐film nanocomposite membranes

Abstract: Nanoparticle (NP) additions can substantially improve the performance of reverse osmosis and nanofiltration polyamide (PA) membranes. However, the relative impacts of leading additives are poorly understood. In this study, we compare the effects of TiO2 and SiO2 NPs as nanofillers in PA membranes with respect to permeate flux and the rejection of organic matter (OM) and salts. Thin‐film nanocomposite (TFN) PA membranes were fabricated using similarly sized TiO2 15 nm and SiO2 (10 – 20 nm) NPs, introduced at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The obtained data are also confirmed by the previous research, where it was shown that the addition of hydrophilic particles into the polymer matrix increased the stratification during membrane preparation due to increased thermodynamic instability [ 47 ], which resulted in membrane with higher porosity, pore radius, and surface porosity. This indicates that the addition of TiO 2 in PA modified the pore system of the membrane and changed its hydrophilicity and pore structure, causing an increase in membrane pure water and water solution permeability [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained data are also confirmed by the previous research, where it was shown that the addition of hydrophilic particles into the polymer matrix increased the stratification during membrane preparation due to increased thermodynamic instability [ 47 ], which resulted in membrane with higher porosity, pore radius, and surface porosity. This indicates that the addition of TiO 2 in PA modified the pore system of the membrane and changed its hydrophilicity and pore structure, causing an increase in membrane pure water and water solution permeability [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…As membrane permeability (and thus surface pore size) increases compared to the pristine PA membrane, it may promote increased availability of the selective layer structure for the pollutant (coolant lubricant) facilitating its penetration inside the pores [ 49 ]. However, the optimal content of TiO 2 (0.3%) in the PA matrix forms a balance between surface hydrophilicity, roughness, and pore size of the membrane, maintaining high performance (fluxes) and FRR [ 29 ]. Despite the increase in surface hydrophilicity of the PA/TiO 2 (0.5 and 0.75 wt.%) membranes, their higher surface roughness compared to the PA and PA/TiO 2 (0.3 wt.%) membranes ( Table 1 ) caused an increase in the specific area of the selective layer for the adsorption of coolant lubricant molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the preparation of nanocomposite membranes is easy to realize, subsequently reducing the cost for fabricating membranes. Diverse nanofillers have been incorporated into the separation layer of the thin film composite (TFC) nanofiltration membranes, including nonporous nanofillers (e.g., metallic oxide, 12,13 graphene oxide [GO], 14 organic fillers 15 ), porous nanofillers (e.g., metal organic frameworks (MOF), 16 covalent organic frameworks (COF), 17 porous organic polymers 18,19 ), and hollow nanomaterials (e.g., halloysite nanotubes, 20 carbon nanotubes, 21 and hollow polymeric nanoparticles 22 ). Janus nanoparticles used as nanofillers have been reported for gas separation membranes, 23 fuel cell membranes, 24 and ultrafiltration membranes, 25 while the study on nanofiltration membranes was limited.…”
Section: Introductionmentioning
confidence: 99%